2021
DOI: 10.1002/elan.202060598
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Innovative Nitrite Sensing Platform Based on the Construction of an Electrochemical Composite Sensor of Polymer Coated CNTs and Decorated with Magnetite Nanoparticles

Abstract: Electrochemical determination of nitrite in real water samples is achieved using simple and efficient electrochemical sensor. The sensor is fabricated by electrodeposition of a thin layer of poly(3,4‐ethylenedioxythiophene) sandwiched by drop‐casting two thin layers of CNTs and iron oxide nanoparticles (Fe3O4) over a GC electrode surface. Voltammetry determination of nitrite in tap water and wastewater samples in the concentration range (0.5–150 μM) is successfully achieved with detection limits of 22 and 24 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…DL and QL are determined according to (S/N = 3). 46 The performance of the sensor for TFLP detection is compared with other cited modied sensors. 2,3,37,44,[47][48][49] The sensor offers reasonable linear range for TFLP detection, DL lower than other used modied electrodes with good stability and accuracy as illustrated in ESI Table 2.…”
Section: Robustnessmentioning
confidence: 99%
“…DL and QL are determined according to (S/N = 3). 46 The performance of the sensor for TFLP detection is compared with other cited modied sensors. 2,3,37,44,[47][48][49] The sensor offers reasonable linear range for TFLP detection, DL lower than other used modied electrodes with good stability and accuracy as illustrated in ESI Table 2.…”
Section: Robustnessmentioning
confidence: 99%
“…[32][33][34][35][36][37][38] CNTs modified with different materials reported in the literature for electrochemical sensing of different compounds. [39][40][41][42][43][44] Beta cyclodextrin (β-CD) molecule has a cylinder-shape; the presence of hydroxyl groups at the outer surface of the molecule is responsible for its hydrophilic character while the inner surface is hydrophobic in nature. [45,46] The cyclodextrin's cylindrical shape allows the guest molecule to be kept within the hydrophobic interior while the exterior of the cyclodextrin is hydrophilic and soluble in aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…Several published studies have reported the design and synthesis of such MOF-based composites for electrochemical purposes, and a range of conducting polymers including polyaniline (PANI), poly­(3,4-ethylenedioxythiophene) (PEDOT), polypyrrole, and polythiophene have been utilized as the conductive materials. Among these conducting polymers, PEDOT has been reported as the active material for electrochemical nitrite sensors. We thus reasoned that the nanocomposite consisting of a highly porous and electrocatalytic porphyrinic Zr-MOF and the conductive PEDOT should further enhance the sensing performances of both pristine materials toward nitrite.…”
Section: Introductionmentioning
confidence: 99%